A study on ferns as carving motives in the Polynesian community involving the New Zealanders Maori, Indonesian Minangkabau & Malaysian Malay - Mohd. Yaman, Maheran ([s.n.], 2011)
This study is an early observation in the period of two months from the perspective of a Malay Muslim who has never been to New Zealand. The topic is related to the discipline of architecture as well as landscape architecture. It suggests the link between plant species, fern, with the cultural habits and values of Polynesian communities in New Zealand and the Malays in Sumatra, Indonesia, and in Peninsular Malaysia. From a view of a cultural landscape perceptions, this study produce a comparisons on fern as an emblem with a comparisons of carving motif using ferns in other Polynesian community such as Maori in the aninism society in New Zealand, Malay in Malaysia and Minangkabau in Indonesia as the Islamic society. It is important to study the relationship of fern and carving in the Polynesian and Malay architectures in order to see how environment influenced the society. Moreover, how the environment is use as tool or metaphor to educate society. In term of human geography, the sea farers origins of Maori in New Zealand and Malays in the Malay Archipelago can be traced by the sea route around Polynesian island. Though differs in religion the Polynesian have similarities. This is seen in the use of ferns as the carving motives as demonstrate in this study.